Bridging the Digital Divide: A Need Analysis for FlipHTML5-Based Academic Writing E-Modules with a Student-Centered Learning Approach - Alhadj, Dafran; Nurhayati, Nurhayati; Purnomo, Mulyadi Eko; Ernalida, Ernalida (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the needs of students and teachers for the development of FlipHTML5-based academic writing e-modules with the Student-Centered Learning (SCL) approach as the initial stage in the Dick and Carey R&D model. The study involved 109 students of class X who were determined through purposive sampling. Data were collected through needs analysis questionnaires, semi-structured interviews, and class observations, then analyzed descriptively, quantitatively, and qualitatively. The results show a striking gap between the availability of conventional materials and the learning preferences of Generation Z students, where 98% of students need multimodal teaching materials that are easily accessible through digital applications to reduce the cognitive burden in understanding writing materials. The integration of the SCL approach is also proven to be urgent to support learning independence. These findings confirm the need for the immediate development of interactive e-modules as a strategic pedagogical solution to improve academic writing competence.